2018
DOI: 10.5039/agraria.v13i3a5557
|View full text |Cite
|
Sign up to set email alerts
|

Predation of diamondback moth larvae and pupae by Euborellia annulipes

Abstract: Diamondback moth, Plutella xylostella, is considered the most important pest species of brassica crops and Euborellia annulipes can exhibit potential for its control. This work recorded the consumption of 4 th-instar larvae and pupae of P. xylostella by nymphs and adult females of the ring-legged earwig E. annulipes at different ages: 2, 4, 6, 8 and 10 days old. Nymphs in the 3 rd-instar and females of E. annulipes consumed daily more P. xylostella larvae than pupae. The consumption of diamondback moth pupae b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…As predicted, E. annulipes females were more voracious than males, as they consumed larger numbers of fruit fly larvae or pupae, in agreement with the aggressive behaviour of females previously reported for earwigs (Moral, Demetrio, et al, 2017; Nunes et al, 2018; Oliveira, Alves, et al, 2019). Earwig females likely require more food because they are larger than males and require more energy to produce eggs and provide maternal care (Rankin et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As predicted, E. annulipes females were more voracious than males, as they consumed larger numbers of fruit fly larvae or pupae, in agreement with the aggressive behaviour of females previously reported for earwigs (Moral, Demetrio, et al, 2017; Nunes et al, 2018; Oliveira, Alves, et al, 2019). Earwig females likely require more food because they are larger than males and require more energy to produce eggs and provide maternal care (Rankin et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to other species of earwigs (Oliveira, Alves, et al, 2019; Tangkawanit et al, 2021), our study showed that E. annulipes preyed more on larvae than on pupae. Other studies have reported that E. annulipes prefers to consume larvae over pupae of a lepidopteran prey (Nunes et al, 2018; Nunes, Dantas, et al, 2019; Nunes, Paulo, et al, 2020). The higher predation capacity of earwigs for insect larvae is likely related to the hardness of the tegument, which is harder in the pupal than in the larval stage, acting as protection against natural enemies (Kalinoski & DeLong, 2015).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Doru luteipes has been recognized as a generalist predator of lepidopteran eggs and larvae in maize, soybean, sugarcane, and B. oleracea crops [47][48][49]58,59]. Natural occurrence and predation of P. xylostella by the earwig species Euborellia annulipes (Dermaptera: Anisolabididae) has been reported in kale crops and intercrops with Lobularia maritima (Brassicaceae) [60]. This lack of preference for P. xylostella could be due to the origin of the earwigs used in this study, as they were from maize and sugarcane plantations, where S. frugiperda is a big part of their diet.…”
Section: Discussionmentioning
confidence: 99%
“…Earwigs were found to be predators in cruciferous crops, such as cabbage in The Philippines (Basedow, 1993) and collard greens in Brazil (Ribeiro & Gontijo, 2017). The ringlegged earwig, Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae), is considered to be one of the most cosmopolitan species (Kocarek et al, 2015) and, although it is omnivorous, some researchers have reported this insect as a predator of lepidopteran pests, such as Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) and P. xylostella (Silva et al, 2009;Moral et al, 2017;Nunes et al, 2018). However, there are few studies evaluating the predation behavior of E. annulipes and its effect on economically important insect pests.…”
Section: Introductionmentioning
confidence: 99%